(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This survey was done to inform about the benefits of vision therapy for eye diseases in selected villages of Taluka in Anand district and to inform about the damage to eyes caused by electric devices. In which people from 5 years to 60 years of age were given form-based information. About eye disease and damage caused by electric devices and how to keep eyes safe through vision therapy, but very few people knew about vision therapy and eye disease. For this, many efforts are required.